Labor Market Outcomes of Same-Sex Couples in Countries with Legalized Same-Sex Marriage - Honorata Bogusz; Jan Gromadzki (Institute of Labor Economics (IZA), 2024)
We study the labor market outcomes of same-sex couples using data from large household surveys that represent more than two-thirds of the world's population with access to same-sex marriage on three continents. Same-sex couples are less likely to be inactive and work more hours than different-sex couples, largely due to the differences in the probability of having a child. Men in same-sex couples are up to 60 percent more likely to be unemployed than men in different-sex couples. These unemployment gaps cannot be explained by occupational sorting or other observable characteristics.
Keywords: J15; J16; J22; J23; 330; labor supply; unemployment; same-sex couples; discrimination; LGBTQ; parenthood